Negative attitudes among short-term stroke survivors predict worse long-term survival. - Lewis, S; Dennis, MS; O'Rourke, S; Sharpe, M (2001)
BACKGROUND AND PURPOSE: Patients respond to serious illness in different ways. We wished to determine whether different attitudes toward illness are associated with survival after stroke. METHODS: Three hundred seventy-two stroke patients were identified and medically assessed as part of a randomized trial to evaluate a stroke family care worker. They had all survived 6 months from randomization. A research psychologist visited each patient and administered the Mental Adjustment to Stroke Scale (a self-rated attitude scale based on the Mental Adjustment to Cancer Scale). Disability and dependence (Barthel Index, modified Rankin Scale) and mood (Hospital Anxiety and Depression Scale, General Health Questionnaire 30) were also assessed. Patients were followed up in 1998 (3 to 5 years after the initial stroke) to establish their survival. We modeled the relationship between Mental Adjustment to Stroke scores and survival, adjusting for other factors associated with stroke survival. RESULTS: Eighty-two patients (22%) died within 3 years. After adjustment for other significant factors, fatalism and helplessness/hopelessness were both associated with decreased survival (P=0.03 and 0.04, respectively), but fighting spirit, anxious preoccupation, and denial/avoidance were not. Mood was not associated with survival. CONCLUSIONS: Patients' attitudes toward their illness seem to be associated with survival after stroke. Patients who feel that there is nothing they can do to help themselves 6 months after a stroke have a shorter survival. These findings need to be confirmed and any causal relationship between attitude and survival further explored in a randomized controlled trial to "improve" the attitude of stroke patients toward their illness.